Processos de colheita e pós-colheita na Fazenda Rancho Grande para obtenção de cafés de qualidade - Duarte, Thaylor Rodrigues (2013)
Agribusiness in Brazil is responsible for 42% of total exports and 37% of brazilian jobs . The coffee was and still is, for various producing regions , one of the activities with the greatest capacity to generate jobs and fixing of manpower in the field , enough to employ about 3.5 million people , thus having a high economic value . So we need to take some care in the process of harvesting and post -harvest so you get a good quality coffee , because the consumer is becoming more demanding , thus forcing the improvement of activities before the preparation of coffee. Thus we carried out a comparative study between various processes of harvesting and post -harvest on Rancho Grande Farm, to identify factors that influence product quality coffee. Among the factors analyzed , it is shown that care in harvesting , receiving, drying and storage of coffee, will be the essence to achieve a better quality . The objective of the present work a set of care , processes of harvesting and post -harvest coffee , which will certainly help producers address the shortcomings in care for coffee , to improve coffee quality . There was a considerable increase in product quality coffee, which went on to produce 78 % of cafes pulped , and in turn a value added to the final price as well as the entry of new domestic and international buyers.